THE MEDIATING ROLE OF WORKPLACE HAPPINESS IN THE EFFECT OF LEADERSHIP, ORGANIZATIONAL CLIMATE AND CYBERBULLING ON EMPLOYEE PERFORMANCE - Sari, Indah Purnama; Mas’ud, Fuad (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
This study aims to analyze the mediating role of workplace happiness in the influence of leadership, organizational climate and cyberbulling on employee performance. This research uses associative survey quantitative research. The population in this research is all employees of Batik Temawon MSMEs Semarang totaling 66 employees. In this study, the sampling technique was to use a saturated sample of 66 employees. The results of the analysis show that work environment and handling cyberbullying have a significant positive impact on workplace happiness and employee performance. In contrast, leadership does not significantly affect workplace happiness and the relationship between leadership, workplace happiness and employee performance does not prove significant. This analysis can serve as a basis for companies to identify factors that need to be improved or addressed to increase employee happiness and performance, with leaders empowered to understand and capitalize on their direct impact on workplace happiness levels. Organizations are also expected to raise awareness of the work climate, encourage the adoption of policies that support employee well-being, and conduct periodic evaluations to identify areas for improvement. In addition, addressing cyberbullying in the workplace is essential, given its negative impact on employee happiness and performance. Organizations can respond by designing clear and effective policies and conducting training programs to raise employee awareness of cyberbullying. To increase happiness in the workplace, organizations can implement programs and activities that support work-life balance, as well as provide resources to manage stress and improve employees' personal well-being.